Worker Safety Improvement at Paper Pleating Production Line Using Poka-Yoke Concept - A Case Study in Automotive Industry / Ahsana Aqilah Ahmad ...[et al.] - Ahmad, Ahsana Aqilah; Rashid, Amirul Abd; Wong, Freddawati Rashiddy; Iqbal, Muhammad (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
For any industry, every worker is entitled to safe and healthy workplace. Laws, acts and regulations have been established by the authorities to ensure the employer conduct proper assessments on safety and health conditions and continuously reduce the hazard risk to protect their employees. One of the common safety issues that can cause injury is due to improper use of tools and equipment to perform the job. On top of that, this issue can also contribute to other waste as well as quality issue in the production line. In this study, Hazard Identification and Risk Assessment (HIRAC) was done on paper pleating production line that assembled air filter product for automotive industry. Based on the assessment, the cutting process had the highest risk score value that triggerred for improvement as to reduce the risk level. Poka-yoke concept, which was considered as one of the engineering control methods, was used to identify the root cause of the problem. The solution of implementing a new cutting tool design significantly reduced the risk by more than 55%. The new process also made the pleating process became easier to handle; hence, it increased the production linearity and improved the product quality.